2000
DOI: 10.1159/000012416
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity and Burnout in the Medical Profession: An Italian Study of General Practitioners and Hospital Physicians

Abstract: Background: Burnout and psychological stress symptoms represent a major problem among health care professionals. The aim of this study was to investigate the prevalence of and the relationship between psychiatric morbidity and burnout among a convenience sample of Italian primary care physicians (GPs) and hospital physicians (HPs). Method: The sample consisted of 328 physicians (182 GPs and 146 HPs) who completed the 12-item version of the General Health Questionnaire and the Maslach Burnout Inventory (MBI). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
102
5
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 16 publications
13
102
5
14
Order By: Relevance
“…Low PA instead was less representative. Prevalence of estimated psychiatric morbidity was not significantly higher in physicians (36.4%) than in nurses (28.8%), but both were higher than the general Italian population (22.3%; Politi et al, 1994) or the general and hospital physicians (20.3 and 24.3%; Grassi and Magnani, 2000). The previously mentioned study on hospital nurses (Tabolli et al, 2006) found 34% of estimated psychiatric cases.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Low PA instead was less representative. Prevalence of estimated psychiatric morbidity was not significantly higher in physicians (36.4%) than in nurses (28.8%), but both were higher than the general Italian population (22.3%; Politi et al, 1994) or the general and hospital physicians (20.3 and 24.3%; Grassi and Magnani, 2000). The previously mentioned study on hospital nurses (Tabolli et al, 2006) found 34% of estimated psychiatric cases.…”
Section: Discussionmentioning
confidence: 70%
“…Comparison with a representative Italian sample (Grassi and Magnani, 2000) of 328 hospital physicians and general practitioners revealed small differences: high EE was 27%, high DP was 25% and low PA was 13%. In a recent study of 242 Italian hospital nurses (Tabolli et al, 2006), the mean values of the three MBI subscales were similar to those found in this survey (EE ¼ 18.4, DP ¼ 3.9 and PA ¼ 38.1).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A szomatikus egészség vizsgálatakor ugyanis a nemzetközi szakirodalom hangsúlyozza, hogy az orvosok hivatásukból adódóan jobban ismerik a megelőzés és az egészségmegőrzés módszereit, az esetleges problémák korai felismerését, kezelési lehetőségeit. Ugyanakkor az orvosi hivatás emocionálisan és fi zikálisan megterhelő jellege mintegy "predesztinálhat" az egészségi problémák nagyobb arányú megjelenésére [29,30,31].…”
Section: Megbeszélésunclassified
“…[9][10][11][12][13] Burnout has been characterized among health professionals by high levels of emotional exhaustion and depersonalization and decreased levels of personal accomplishment. Burnout is closely related with dissatisfaction at work, [6][7][8] bad quality of care, 12,[14][15][16] or intention to withdraw from practice.…”
mentioning
confidence: 99%